Surface-induced vibrational energy redistribution in methane/surface scattering depends on catalytic activity - Floß, Patrick; Reilly, Christopher S.; Auerbach, Daniel J.; Beck, Rainer D. (Frontiers in Chemistry, 2023)
Recent state-to-state experiments for methane scattering from Ni(111) and graphene-covered Ni(111) combined with quantum mechanical simulations suggest an intriguing correlation between the surface-induced vibrational energy redistribution (SIVR) during the molecule/surface scattering event and the catalytic activity for methane dissociation of the target surface. Here, we report new, quantum state and angle resolved measurements for methane scattering from Ni(111) and Au(111) probing the extent of 𝜈3 → 𝜈1 antisymmetric-to-symmetric conversion of methane stretching motion for two surfaces with different catalytic activities.Consistent with expectations, the extent of SIVR on the more catalytically active Ni(111) surface as measured by the 𝜈1 : 𝜈3 scattered population ratio is found to be several times stronger than on the more inert Au(111) surface. We present as well additional insights on the rovibrational scattering dynamics contained in the angle and state resolved data. The results together highlight the power of state-resolved scattering measurements as a tool for investigating methane-surface interactions.